Modification of morphology of PS/LDPE/ Mg(OH)2 and PS/LDPE/SBS/Mg(OH)2 polymer composites by supercritical CO 2 - (:unkn) unknown (My University, 2011)
In this paper we explore a supercritical carbon dioxide processing method that utilizes CO2 to disperse Mg(OH)2. The structure and properties of the composites are characterized using a scanning electron microscopy (SEM), Differential scanning calorimeter (DSC) and Energy dispersive X-ray spectroscopy (EDS). Furthermore, PS/LDPE/SBS/Mg(OH)2 polymer composites were subjected to examinations to obtain their tensile strengths, elasticity modulus, % elongation, Izod impact strength, hardness, Heat deflection temperature (HDT), Vicat softening point and Melt flow index (MFI). © MD Publications Pvt. Ltd.
Keywords: Kimya; Fizikokimya; Polimer Karakterizasyonu; Temel Bilimler; Mühendislik ve Teknoloji; Chemistry; Physical Chemistry; Characterization of Polymers; Natural Sciences; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Temel Bilimler (SCI); Malzeme Bilimi; MALZEME BİLİMİ, ÇOKDİSİPLİNLİ; POLİMER BİLİMİ; Engineering, Computing & Technology (ENG); Natural Sciences (SCI); MATERIALS SCIENCE; CHEMISTRY; MATERIALS SCIENCE, MULTIDISCIPLINARY; POLYMER SCIENCE; Polimerler ve Plastikler; Fizik Bilimleri; Malzeme Kimyası; Polymers and Plastics; Physical Sciences; Materials Chemistry; Polyethylene; Polymer composites; Polystyrene; Styrene butadiene styrene; Supercritical carbon dioxide